Associated Factors of Primary Enuresis Among Children and Adolescents in Amhara Region, Northwest, Ethiopia, 2016 - Amare, Tadele; W/Michael, Bethelhem; G/HIwot, Birhane; Zewde, Fisseha (Journal of Pediatric Nephrology, 2018)
Introduction: Primary enuresis is the most common elimination disorder in children and adolescents aged 5-17 years worldwide. It often results in psychological, social, and financial problems. This disorder is understudied in less affluent countries. Objective: This study was done to assess the prevalence and associated factors of primary enuresis in children and adolescents in Bahir-Dar Town, Ethiopia. Materials and Methods: This cross-sectional community-based study was conducted in children and adolescents from May to July 2016. A total of 1547 subjects were selected using a multistage sampling technique. Data were collected using DSM-5 criteria and the Strengths and Difficulties Questionnaire (SDQ). Results: A total of 1520 participants were involved in the study with a response rate of 98.25%. The prevalence of primary enuresis was 8.6%. Age range 5-8 years [AOR=10.35, 95% CI (3.468, 30.875)], deep sleep [AOR=2.18, 95% CI (1.192, 3.983)], and conduct problems [AOR=5.98, 95% CI (3.341, 10.694)] were significantly associated with primary enuresis. Conclusions: Factors that affect primary enuresis are young age, deep sleep, snoring during sleep, sleeping more than two hours a day, and conduct problems. Therefore, special attention should be given to children and adolescents about primary enuresis prevention. Keywords: Primary enuresis; Child; Adolescent